Press for women in Ukraine: history, types and prospects - Kitsa, Mariana O.; Mudra, Irina N. (Journal of the Belarusian State University. Journalism, 2019)
The article considers the theory and history of the functioning of women’s periodicals in Ukraine from the beginning of the XX century up to the present. A comparative analysis of periodicals for women has been carried out, a classification of modern women’s magazines has been made. A survey was conducted on the attitude of the readership to publications for women, and trends and prospects for the functioning of printed publications for women in the near future have been identified.